Negotiating Moral Experiences, Contested Relations, and Housed Futures in the Context of Health and Social Service Use by Persons Experiencing Homelessness - Amelie Perron; Chad Hammond; Brianna Hammond; Liquaa Wazni; Fiona Jager; Katharine Larose-Hébert; Jean Daniel Jacob; Dave Holmes (International Journal on Homelessness, 2026)
Housing has been identified as a social determinant of health, and its impact on people’s well-being, autonomy, sense of connection, safety and social participation have been established. Canada is currently encountering a housing crisis with homelessness as its sharpest edge with significant numbers of people experiencing homelessness and growing demands for shelters and other services. This project used a qualitative approach to explore the complex interplay of factors that shape experiences of homelessness, specifically with regard to accessing support systems and transitioning into stable housing situations. Twenty-seven individuals experiencing homelessness participated in in-depth interviews, each analyzed using Interpretive Phenomenological Analysis. Three superordinate themes were developed from the interviews, including: 1) Homelessness as a moral experience, 2) The double edge of supportive services, and 3) Managing apprehensions and mobilizing resources towards a housed future. These themes highlight the precarity of fairness, justice, and dignity within relationships between persons experiencing homelessness and service staff. Findings from the study have valuable implications as they reveal the importance of a moral ground that preserves respect, trust, and dignity within spaces of support service delivery for people experiencing homelessness.